The ecology of lacertids at Gibraltar - Cortés, J (1984)
﻿ Behavioural and ecological studies on southern European reptiles have been few. Knowledge even of the distribution and habitat requirements of the herpetofauna of southern Iberia is limited. The reptile fauna of Gibraltar was studied in relation to the history of the habitats, and compared to that of the region. Habitats, climate, and relevant aspects of microclimate are described. Work-centred on the Iberian Wall Lizard Podarcis hispanica which where possible was compared to Psammodromus algirus with which it sometimes occurred. Data were collected from lizards captured in the field and kept in captivity, which were used in experiments, and from transect and continuous observations in the wild. Morphology, use of microhabitat, height and substrate preferences, annual activity, emergence, temperature relations, metabolism and behaviour were investigated. Where possible, comparison was made between lizard size classes and sexes. The observational and experimental data suggest that Gibraltar P. hispanica are well adapted to their environment. Using a variety of thermoregulatory methods they can maintain fairly uniform body temperature throughout the year. They appear to change their distribution in the habitat seasonally in response to the need for food and shelter. Activity is most severely restricted during the hottest part of the day in summer and in overcast weather. It is suggested that P. hispanica is an opportunistic feeder consuming a variety of small invertebrates during bouts of foraging which vary in length and frequency according to time of year. Lizards are tolerant of each other outside the breeding season, when males become aggresive towards each other and females and juveniles show more appeasement behaviour. The results for P. hispanica are discussed in relation to existing work on other lizards, especially lacertids from more northerly locations in Europe.